2021
DOI: 10.2147/copd.s311714
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Antimicrobial Susceptibility of Pseudomonas aeruginosa and Acinetobacter baumannii Complex Isolates in Intensive Care Patients with Chronic Obstructive Pulmonary Disease and Community-Acquired Pneumonia in Taiwan

Abstract: Purpose Little is known about the features and implications of Pseudomonas aeruginosa (PA) and Acinetobacter baumannii complex (ABC) isolates discovered in patients with chronic obstructive pulmonary disease (COPD) and community-acquired pneumonia (CAP) requiring invasive mechanical ventilation and admission to an intensive care unit. Thus, our study aimed to investigate the clinical characteristics and antimicrobial susceptibilities of PA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that the invasiveness of A. baumannii and P. aeruginosa is higher than that of other NFGNB. 17 P. aeruginosa meningitis is much complicated to treat due to the existence of the quorum sensing system and biofilm formation, 18 which can induce drug resistance and lead to an increase in mortality. The carbapenem resistance rate of P. aeruginosa can be up to 30%, and the resistance rate of imipenem is even higher than that of meropenem.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the invasiveness of A. baumannii and P. aeruginosa is higher than that of other NFGNB. 17 P. aeruginosa meningitis is much complicated to treat due to the existence of the quorum sensing system and biofilm formation, 18 which can induce drug resistance and lead to an increase in mortality. The carbapenem resistance rate of P. aeruginosa can be up to 30%, and the resistance rate of imipenem is even higher than that of meropenem.…”
Section: Discussionmentioning
confidence: 99%
“…20 Of note was the high number of respiratory infections among outpatients which agrees with other studies in which this kind of A. baumannii infections are the most common on community patients. 20 Although community-acquired infections are less common than those acquired in a hospital, they have been described in different geographical areas [20][21][22][23] and are considered of special concern owing to related poor outcomes, especially with risk factors such as alcoholism or chronic obstructive pulmonary disease. 20,22 The lack of data concerning previous admissions might explain several outpatient infections as actually being hospital acquired; however, the differences in antibiotic resistance from in-and outpatients, as well as the differences in the evolution of MDR/XDR isolates in both populations, suggest a different origin and support the presumption of a truly communityacquired A. baumannii.…”
Section: Discussionmentioning
confidence: 99%